中部地區公立國小附設幼兒園增置教保員人力運用現況與差異調查研究 - 林淑媛(Shu-Yuan Lin); 蔣姿儀(Tzu-Yi Chiang) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2018)
The purpose of this study is to understand the situation of manpower utilization of educare givers in the affiliated preschools of public primary schools in the central region of Taiwan. The study also examines the differences of manpower utilization among different counties in the central region of Taiwan by adopting a survey method with the use of a researcher-developed questionnaire. After collecting a total of 813 valid questionnaires, the data are statistically analyzed using descriptive statistics and test of homogeneity of proportions. Findings from this study indicate that the manpower utilization of additional educare givers is the highest in childcare work, followed by teaching, and the lowest is in administrative work. The proportion of assistance that the educare givers provides is the highest on “guide and care for daily life” in child-care work, on “collaborative teaching” in teaching work, and on “health care business” in administrative work. Statistically significant differences exist among th